GANZ: “Gerakan Anti Narkoba” through the Game of Guess the Picture for Students at SMP Kalam Kudus, Abepura - Mona Safitri Fatiah; Muhammad Fajar Aswad Nugroho; Cornelia Hanata Delizea; Ade Alwi Imbiri; Ruth Bugerom; Agnes Tegai; Milla Gori Wendani; Kristina Ansek; Rosa Simatauw; Sarni Rante Allo Bela (Universitas Muhammadiyah Surakarta, 2025)
Substance abuse involving narcotics, psychotropics, and other addictive substances (NAPZA) among adolescents remains a public health concern in Jayapura City. Preliminary observations at Kalam Kudus Junior High School revealed that most students had limited knowledge regarding the dangers of substance abuse, while the available educational media remained conventional and less engaging for adolescents. This Community Service Program (PKM) aimed to improve students’ knowledge and attitudes toward the dangers of NAPZA through an educational picture-guessing game, implemented in the activity entitled GANZ: Gerakan Anti-NAPZA (Anti-NAPZA Movement). The program was designed using a Participatory Action Research (PAR) approach and conducted among 57 students at Kalam Kudus Junior High School on April 11, 2025. The intervention consisted of four stages: (1) identification of target groups, (2) health education and sharing sessions, (3) pre- and post-test data collection, and (4) implementation of the educational picture-guessing game. Data were collected using pretest and posttest questionnaires and analyzed with STATA 16. Results showed a 29.9% increase in knowledge and a 25% improvement in positive attitudes toward NAPZA prevention after the intervention. The picture-guessing game proved effective in enhancing adolescents’ knowledge and attitudes regarding the dangers of NAPZA. For sustainability, it is recommended that interactive educational media be integrated into school-based programs, alongside continuous collaboration with teachers and parents, to foster a supportive learning environment for NAPZA prevention among adolescents.